Effect of cardiac shock wave therapy plus optimal medical therapy on rehospitalization in patients with severe coronary artery disease: A meta-analysis and trial sequential analysis - Li, Peng; Jia, Na; Liu, Bing; He, Qing (Frontiers in Cardiovascular Medicine, 2022)
Objective Several small sample-sized clinical studies have demonstrated that cardiac shock wave therapy (CSWT) might reduce the risk of rehospitalization in patients with severe coronary artery disease (CAD). However, other observational studies did not reported that clinical benefit of CSWT. Therefore, the effect of CSWT plus optimal medical therapy (OMT) on rehospitalization is still controversial. Methods We performed an updated meta-analysis and systematic review of randomized clinical trials (RCTs) and prospective cohort studies identified in systematic searches of Pubmed, Embase, the Cochrane library, the ClinicalTrials.gov website and Chinese SinoMed Database (up to December 2021). Primary endpoint was the rate of major adverse cardiac events (MACE, the composite outcome of mortality, coronary artery revascularization, and rehospitalization). Meta-regression and subgroup analyses were used to identify possible contributors to between-study variances in the HDRS. Required information size (RIS) was calculated with trial sequential analysis (TSA). Results A total of 11 RCTs and 5 prospective cohort studies involving 1149 patients with a mean follow-up of 10.6 months (range 3–72) months were included. Overall, CSWT plus OMT significantly decreased the rate of MACE compared with the OMT group (RR, 0.39; 95%CI, 0.29–0.53), which was mainly attributed to markedly lower risk of rehospitalization (RR, 0.37; 95% CI, 0.27–0.51). Subgroup analysis showed that the pooled RR was significantly lower in studies enrolling patients with higher baseline Canadian Cardiovascular Society angina class (≥2.2) (RR, 0.36; 95% CI, 0.26–0.50). TSA showed that The RIS for MACE was 935, and the accrued information size was 577. Conclusions CSWT plus OMT could decrease the rate of rehospitalization among patients with severe CAD. However, this result must be interpreted with caution, for the evidence supporting the use of CSWT for severe CAD is limited by the small sample size and short follow-up period of previous studies. Larger RCTs with longer follow-up are warranted to confirm these findings.